A surgical management of articular disc injury in temporomandibular Joint: A compiled case series of two cases with articular disc tear managed with surgical intervention - Sinha, Devanshu; Seetaram, Mahima; Ramakrishnan, Karthik; Narayanan, Vivek; Juliet, Melita (Indian Journal of Case Reports, 2024)
Articular disc injury in the temporomandibular joint (TMJ) can lead to significant pain and limited jaw movement. We present two cases in this case series of articular disc injuries in the TMJ and elaborate on their etiology, clinical presentation, diagnostic modalities, and treatment provided with follow-up reviews. Case 1 involved a 50-year-old female with a history of pain and clicking in the left TMJ for 10 years, wherein imaging studies revealed a discal tear. Case 2 involved a patient who presented with trauma and was diagnosed with a displaced disc with a disc tear when the patient was screened for mandibular fractures. The patients underwent surgical intervention, and the disc tear was repaired, following which both showed marked improvement. Our cases highlight the importance of early diagnosis and necessary surgical management of articular disc injury in the TMJ for better clinical outcomes.